Regulation of dopamine release by striatal GABA and acetylcholine in health and disease - Lopes, EF (2019)
Dopamine (DA) signalling plays a central role in the normal functions of the basal ganglia, by helping facilitate behavioural processes such as action selection and reinforcement learning. Dysregulation of DA signalling is implicated in a diversity of neurological and psychiatric disorders including Parkinson’s disease and addiction.